Sharing the wonder of birds with kids - Erickson, Laura, 1951- (University of Minnesota Press, 1997)
On the wings of Laura Erickson's award-winning book For the Birds comes Sharing the Wonder of Birds with Kids. Easy and fun to use, Sharing the Wonder is a delightful book that helps caring adults introduce kids to the fascinating world of birds. Chock-full of creative activities, this hands-on guide goes way beyond teaching bird identification. In her light-hearted style, Laura paves the way for children to discover--with a little help from you--the beauty and significance of birds, how their bodies work, why they behave as they do, and why it's critical to protect and care for them. Sharing.